Multiverktyg mot ekonomisk och organiserad brottslighet: Skript, situationell prevention, rutinaktivitet, brottsmönster - Korsell, Lars; Lundin, Henrik; Gripenklinga, Madelene (Nordisk Tidsskrift for Kriminalvidenskab, 2025)
Abstract: The article suggests combining script analysis and crime prevention theories to tackle economic and organised crime. These forms of crime often consist of a series of interconnected steps – like a script – and usually occur within the context of complex legal or illegal operations. By using script analysis, the crime process is broken down into a series of steps, including preparation and follow-up work. With the various steps of the crime process revealed, the next phase is to identify appropriate crime prevention measures. In this part of the analysis, it is beneficial to apply routine activity theory, situational crime prevention, and crime pattern theory. The combination of script analysis with the aforementioned theories functions as a multitool. This approach has been tested on specific cases across several crime types, for instance, the illegal diesel trade. One study showed that in addition to crime prevention measures, suggestions for detecting criminal activity could also be identified.